Pemasaran dan Pengembangan Outlet PT. Pos Indonesia (Persero) Binjai 20700 - Yuniar Pangesti; Muhammad Ikhsan Harahap (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
PT Pos Indonesia is a State-Owned Enterprise (BUMN) which operates in the delivery services sector. One of the services businesses offer is sending letters and packages. Companies with this delivery service will really need a marketing strategy to attract customers who operate in the business world which aims to satisfy consumers and increase sales volume. The data collection method in preparing the Final Assignment is the method of observation, interviews and documentation studies with the analysis method in the form of qualitative analysis, namely a data analysis method without using statistical analysis. The first thing to do in a marketing strategy is to look at market needs first. Then determine the market segment to be targeted, namely the business market segment. By determining the business market segment, determining the target market determines the strategy for selecting the company. By choosing a target that suits the business market segment, the market position will automatically become the label for the business product itself in society. The marketing mix in a marketing strategy will automatically follow the flow of segmentation, targeting and positioning, this is because the product, place, price and promotion are determined according to the business market segment.